Utilization alternative medicines among patients attending alternative hospitals. - Pandey, Laxmi (2016)
ABSTRACT: Use of Alternative Medicine is increasing globally with a high prevalence equally in the developing countries. Alternative medicine is popular method of treatment because it is perceived as natural, safe and a holistic approach of healing that promotes wellness rather than just a treatment. A descriptive cross-sectional study was conducted to find out utilization of alternative medicine among patients attending alternative hospitals who met the inclusion criteria. Total 210 patients (age >-18 yrs) were interviewed from 15th Falgun to 15th Chaitra, 2072. The obtained data were analyzed using SPSS version 16.0. The findings revealed that the mean age of patients was 45.36+- 15.49 years. Patients with chronic health problem (74.76%), married (85.2), female (63.3%), (75.2%) with higher education (31.6%) were more likely to utilize alternative medicine. The most common problem for utilization of alternative medicine was neuromuscular problem (40.5%). The most common reason for utilization of alternative medicine was family tradition (51.3%). Among the patients who used prescribed medicine, 39.4 percent were using alternative medicine at first. The study unveiled that 75.2 percent were satisfied with Alternative Medicine. There was statistical significance between age of patients (p=0.004), back pain (p=0.003), digestive problems (p=0.006), life style modification (p=0.007), skin problems (p=0.034), and paralysis (p=0.046)with utilization of alternative medicine. Patients use alternative medicine due to family tradition for a long time even though they are little or no benefitted now. They have a strong belief that the action of alternative medicine is slow. It is necessary to integrate alternative medicine with national medical system for providing holistic health service under one roof of the health care system. Alternative medicine should be an integral part of all health care providers. Key Words: Alternative Medicine, Adult Patients, Utilization, Alternative Hospitals